Kyai's Leadership Behavior in Caring for Islamic Boarding Schools: Perilaku Kepemimpinan Kiai dalam Merawat Pondok Pesantren - Muh. Khoirul Rifa'i (Halaqa: Islamic Education Journal, 2020)
The Kiai's behavior in carrying out his leadership prioritizes usefulness and full of affection as well as tolerance to others. The behavior of the next generation of scholars uses deliberation in solving problems. The charism of the Kiai is characteristic and is passed on to his successors. The Kiai's behavior that prioritizes the usefulness is in accordance with the behavior of human relations oriented. To become a leader, preparation is needed starting from yourself later, family and continuing to the community. In essence, a Kiai must be able to show that he has more devotion and is able to implement khoirun nas anfa'uhum linnas. Initially, the cleric was the center of the leadership of the Tebuireng and Hidayatul Mubtadi-ien Islamic boarding schools with charismatic, then the Kiai's leadership in Islamic boarding schools shifted to managerial and situational leadership where the Kiai asked for input from the boarding school officials but the Kiai remained the spiritual leaders of the santri and society.